Circulating endothelial microparticles in female migraineurs with aura. (February 2015) - Liman, Thomas G; Bachelier-Walenta, Katrin; Neeb, Lars; Rosinski, Jana; Reuter, Uwe; Böhm, Michael; Endres, Matthias
Background and purpose: Endothelial microparticles (EMPs) are vesicles that are released from activated endothelial cells and serve as a surrogate for endothelial dysfunction (ED). ED may be involved in migraine pathophysiology and contribute to the increased risk of ischemic stroke, particularly in female migraineurs with aura (MA). We sought to determine whether EMPs are elevated in women with MA. Methods: In this case-control study, EMPs were detected by analysing surface markers using fluorescence-activated cell sorting (FACS). Surface markers were measured covering the main cell lines relevant in cardiovascular disease like endothelial cells, platelets, monocytes and leucocytes. Microparticles (MPs) were identified in correlation to calibration by 1 -µm calibrator beads (Beckman Coulter). Arterial stiffness was assessed using fingertip tonometry and the heart rate-adjusted augmentation index (AI). Results: We included 29 patients with MA and 29 matched controls. MA patients had significantly higher EMPs (CD62E + AnnexinV + : 5142/µl vs 1535/µl; p  < 0.001; CD144 + AnnexinV + : 6683/µl vs 3107/µl; p  < 0.001), monocytic (CD14 + AnnexinV + 6378 vs 3161; p  < 0.001), and platelet MPs (CD62P + CD42b + AnnexinV + 5450 vs 3204; p  < 0.001). Activated EMPs (CD62E + AnnexinV + ) correlated with heart-rate adjusted AI ( r  = 0.46; p  < 001). Conclusion: EMP levels are significantly elevated in women with MA and correlated with increased AI. Our findings suggest that endothelial activation is present in women with MA. This might contribute to higher stroke risk in MA.